Emotional Freedom Techniques (EFT) to Overcome Anxiety in Teenagers with Smoking Behavior - Rahman, Irpan Ali; Nurhayati, Nurhayati; Anggriani, Dewi; Khasanah, Uswatul; Anwar, Syamsul; Apipudin, Aap (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescence is a transition period from childhood to adulthood, where adolescence is marked by physical, psychological and psychosocial changes. states that adolescence is a period that experiences many changes, especially psychological changes that make teenagers emotional and make their psychological state depressed. One complementary therapy that can be used as an alternative is Emotional Freedom Technique (EFT) therapy. The aim of Evidence Based Practice Nursing is to determine the effect of Therapy (EFT) on reducing anxiety levels in adolescents at SMAN 2 Ciamis. This research method uses a Quasy Experiment one group pretest and posttest design approach. The population is teenagers with smoking behavior who experience anxiety at SMAN 2 Ciamis. Using purposive sampling. The number of samples using the Slovin formula was 23 students with inclusion criteria of moderate anxiety levels. The results of the study, before and after the intervention, were assessed using the State-Trait Anxiety Inventory - Trait (STAI-T) anxiety questionnaire to assess whether there was a decrease in anxiety levels before and after the intervention (EFT) with the procedure of tapping or pressing meridian points on body to restore energy balance. The intervention for implementing EFT is carried out within 25-30 minutes, 4 times (2 weeks). From the statistical test results, it was found that there was a significant difference in the results of the first assessment and the second assessment before and after the intervention (EFT) with a p-value of 0.000 (P<0.05). In conclusion, the application of EFT intervention has proven to be effective for adolescents who experience anxiety, this is proven by a decrease in anxiety levels after the intervention.